Analisis Wacana Kebijakan Riset Kemendiktisaintek - Saputra, Gigih (Samsara Institute Publisher, 2025)
Indonesian research has various problems, namely the lack of basic research with major breakthroughs, publication cornering, professoring cornering, very quantitative research standards, and so on. The Ministry of Education, Science and Technology discussed several policies such as the not mandatory publication of Scopus to become a Professor, Indonesian journal publishers prioritize quantity over quality so that only 11 journals are included in Q1 Scopus, and the rampant cornering of professors is the responsibility of the campus. This research is qualitative and the literature study uses the perspective of the newness level of research and the level of thinking Bloom's Taxonomy to provide constructive criticism and recommendations on the discourse of national research policies. This research relies on its specific literature data on reporting in mass media and credible online media. The findings of this research show that research problems need to be solved systematically starting from the research system itself. This research recommends a research system policy in the form of an emphasis on basic research to find new theories, a lecturer career path that leads to the highest level of research novelty, a contribution indicator for the community, placing functional positions as a tool to achieve the best level of novelty and contribution, proportionality of research quantity, and proportionality in viewing reputable international journal indexers. These recommendations are a systemic solution to improve the quality of research and competitiveness in the international arena. On the other hand, these recommendations can reduce the practice of capitalism and feudalism in Education systemically.